2020
DOI: 10.1038/s41598-020-58256-4
|View full text |Cite
|
Sign up to set email alerts
|

Cellular apoptosis and necrosis as therapeutic targets for novel Eugenol Tosylate Congeners against Candida albicans

Abstract: Despite the rise of new Candida species, Candida albicans tops the list with high morbidity and mortality rates. to tackle this problem there is a need to explore new antifungals that could replace or augment the current treatment options. We previously reported that tosylation of eugenol on hydroxyl group resulted in molecules with enhanced antifungal potency. in line with that work, we synthesized new eugenol tosylate congeners (ETC-1-ETC-7) with different substituents on pendent sulfonyl group and tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Further, TUNNEL assay corroborates the apoptotic nature of these three compounds against C. auris cells and the observations are in accord with previous literature, where researchers have documented dose dependent effect of natural compounds on induction of apoptosis and DNA damage in Candida cells [41] , [42] . These findings are also in agreement with our research findings where semi-synthetic compounds were reported to cause dose dependent late apoptosis in C. albicans [5] , [21] .…”
Section: Apoptosis Studiessupporting
confidence: 94%
See 2 more Smart Citations
“…Further, TUNNEL assay corroborates the apoptotic nature of these three compounds against C. auris cells and the observations are in accord with previous literature, where researchers have documented dose dependent effect of natural compounds on induction of apoptosis and DNA damage in Candida cells [41] , [42] . These findings are also in agreement with our research findings where semi-synthetic compounds were reported to cause dose dependent late apoptosis in C. albicans [5] , [21] .…”
Section: Apoptosis Studiessupporting
confidence: 94%
“…For studying apoptotic markers, protoplasts of C. auris MRL6057 were prepared as explained previously [21] . Briefly, cells grown for 8 h were then exposed for 4 h to ¼ MIC, ½ MIC and MIC of test compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antifungal susceptibility testing for Ag–Fe NPs was performed by broth microdilution assay against 25 clinical strains of C. auris , following the Clinical and Laboratory Standards Institute guidelines [ 51 ]. The concentration ranges of Ag–Fe NPs and amphotericin B (positive control) used were 12.5–0.02 µg/mL and 16–0.031 µg/mL, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The compound showed a better activity than the reference drug itraconazole for the Candida strain, and this best activity was observed due to the presence of the p -chlorophenyl group [ 28 ]. Recent studies have indicated the presence of apoptosis in yeast induced by different agents [ 58 , 59 ]. Dying C. albicans cells have been reported to exhibit chromatin condensation, nuclear fragmentation, and DNA damage—the key markers of apoptosis [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%